Teachers working with social emotional competence: students' perspectives on the positive effects - McCuin, Deborah, author; Timpson, William, advisor; Banning, Jim, committee member; Most, David, committee member; Doe, Sue, committee member (Colorado State University. Libraries, 2012)
Research has shown that social emotional learning (SEL) skills help reduce violence, enhance cooperation and problem solving, and foster academic achievement. Teachers with social emotional competence (SEC) develop supportive relationships with students, build on student strengths and abilities, establish behavioral guidelines, coach students through conflicts, encourage cooperation, and model respect and appropriate communication. This qualitative document analysis describes the perceived experience of students positively impacted by a teacher coded as using SEC. Analysis of the traits or qualities of the persons and classrooms they described may impact teacher training and hiring of qualified individuals in the educational setting. Using abductive coding processes, education autobiographies written by 28 undergraduate students at a university in the Midwest were coded for the presence of SEL constructs and traits and attributes of teachers they admired in order to give voice to the perceived experience of students regarding the people and practices that positively impacted them. All of the core constructs of SEL were found to be in evidence and 75% of students cited three or more of the constructs in their documents. Known SEC traits were confirmed by the students' perceived experiences as being impactful as well as opportunities to grapple with issues of social awareness and diversity and teacher investment in the daily activities. Implications on teacher training and hiring of individuals that are capable in creating environments inclusive of safety and belonging, as well as those who are adept at developing relationships both with and among students emerged.
Keywords: social emotional learning; social emotional competence; template protocol; document analysis; emotional intelligence